Clinical Practice Guidelines in Modified Tai Chi Therapy for Post-stroke Dyskinesia - Heilongjiang Association of Rehabilitation Medicine; TANG Qiang; LI Baolong; LI Hongyu; WANG Xue; MU Zichen; PANG Ruifeng; SHA Sha; ZHU Luwen (康复学报)
Stroke is characterized by high morbidity, high disability, high mortality and high recurrence rates. Clinical poststroke dyskinesia seriously affects patients' activities of daily living and quality of life, causing heavy burden to the society and family. Evidence-based medicine has proved that stroke rehabilitation is the most effective way to reduce disability rate. Individualized rehabilitation training programs can not only improve patients' movement disorders and their motivations of training, accelerate the process of rehabilitation after stroke, but also potentially save the medical cost and public health resources. The modified Tai Chi training program is helpful to explore a new path for rehabilitation of post-stroke motor dysfunction by organically integrating the traditional exercise therapy and modern rehabilitation techniques. After many discussions and optimization by experts, the standar-dized modified Tai Chi exercise prescription has been applied to the clinical rehabilitation of limb motor dysfunction in different stages of stroke, and has been proved to have excellent therapeutic effects. The main purpose of establishing the clinical practice guideline of modified Tai Chi therapy is to standardize and guide the clinical management and application, so as to optimize the rehabilitation outcomes. The guidelines explained the modified Tai Chi training therapy in the aspects of terminology and definitions, diagnosis and rehabilitation evaluation standards, clinical application recommendations, safety, implementation norms and precautions, and the references and level of recommendations were illustrated meanwhile. Finally this would be beneficial for the genera-lization and application in rehabilitation practitioners from various levels of rehabilitation institutions, general hospitals or hospitals specialized in traditional Chinese medicine. This guideline has good scientific nature, safety, effectiveness and clinical adaptability.